CROSS-LINGUAL ANNOTATION PROJECTION FOR THE DEVELOPMENT OF MALAY CORPUS - ZAMIN, NORSHUHANI (2014)
Cross-lingual annotation projection methods can benefit from rich-resourced languages to improve the performance of Natural Language Processing (NLP) tasks in less-resourced languages. In this research, Malay is experimented as the lessresourced language and English is experimented as the rich-resourced language. The research is proposed to reduce the deadlock in Malay computational linguistic research due to the shortage of Malay tools and annotated corpus by exploiting stateof- the-art English tools. The aim of the research is to investigate a suitable crosslingual annotation projection based on word alignment of two languages with syntactical differences. A word alignment method known as MEW A (Malay-J;nglish Word Aligner) that integrates a Dice Coefficient and bigram string similarity measure with little supervision is proposed.